Peran Literasi Keuangan dan Kemudahan Teknologi Terhadap Keputusan Menggunakan Layanan E-Wallet Di Kalangan Generasi Milenial - Prabowo, wahyudi; Ghazali, Al; Asep, Asep; Chalimatusadiah, Chalimatusadiah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the role of financial literacy and technological ease on the decision to use e-wallet services among the millennial generation. Digital transformation in the financial sector has introduced various electronic payment service innovations that increasingly facilitate public transactions. Millennials, as technologically adaptive users, have become a primary market segment in the adoption of e-wallets. This research employs a quantitative approach using a survey technique involving 385 millennial respondents aged 25–40 years who actively use e-wallet services. Data analysis was conducted using the Structural Equation Modeling (SEM) method with the assistance of SmartPLS software. The results indicate that financial literacy has a positive and significant effect on the decision to use e-wallets, with a path coefficient value of 0.342 and a t-statistic of 6.847. Technological ease also has a positive and significant effect on e-wallet usage decisions, with a path coefficient of 0.518 and a t-statistic of 9.326. Simultaneously, financial literacy and technological ease explain 68.4% of the variance in e-wallet usage decisions. These findings imply the importance of enhancing digital financial literacy and developing increasingly user-friendly features to encourage broader adoption of e-wallets among millennials. This study provides practical contributions for e-wallet service providers in designing marketing strategies and product development aligned with the characteristics of millennial users.